Perbandingan Intensitas Latihan Berdasarkan Anaerobic Threshold pada Laki-Laki dengan Tingkat Aktivitas Rendah Terhadap Performa Fisik - Rudy Handoyo; Wahyu Wiryawan; Hari Hendriarti Satoto; Sri Wahyudati; Tanti Ajoe Kesoema; I Made Widagda; Erna Setiawati; Rahmi Isma Asmara Putri; Robby Tjandra; Naela Munawaroh; Aditya Paramitha Andini; Ratih Dwiratna Hakim; Arvin Manuel Wulur; Nura Eky Vikawati; Ellena Rachma Kusuma; Mela Kurnia Widyarini; Novritasari Setyaningrum (Medica Hospitalia : Journal of Clinical Medicine, 2025)
Background: Low level of physical activity can reduce physical fitness. Aerobic training can improve physical fitness. A precise aerobic training based on anaerobic threshold (AT) is recommended by American College of Sports Medicine (ACSM) whenever possible. Methods: This was a randomized-single blinded control trial including 24 male subjects with low level of physical activity in Kariadi hospital during December 2023 until February 2024. It was randomized with a sealed envelope. Subjects were allocated in 2 groups (above AT and below AT). Physical performance was measured using SPPB score and muscle endurance that was presented using total repetition of 1RM of knee flexor muscle. Results: There was no significant difference between two groups for total SPPB score (p=0.053). There was a significant difference of muscle endurance between two groups (p=0.010) with the above AT group resulting in higher improvements of muscle endurance (12.00 ± 5.71 vs. 6.67 ± 3.26). Conclusion: Aerobic exercise with intensity based on AT did not show significant differences in total SPPB score. However, aerobic exercise above AT showed a better improvement of muscle endurance in healthy adult men with low levels of physical activity.